2020
DOI: 10.3390/metabo11010024
|View full text |Cite
|
Sign up to set email alerts
|

An Ascophyllum nodosum-Derived Biostimulant Protects Model and Crop Plants from Oxidative Stress

Abstract: Abiotic stresses, which at the molecular level leads to oxidative damage, are major determinants of crop yield loss worldwide. Therefore, considerable efforts are directed towards developing strategies for their limitation and mitigation. Here the superoxide-inducing agent paraquat (PQ) was used to generate oxidative stress in the model species Arabidopsis thaliana and the crops tomato and pepper. Pre-treatment with the biostimulant SuperFifty (SF) effectively and universally suppressed PQ-induced leaf lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 59 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Biostimulants can enhance the tolerance of plants to abiotic stresses and improve productivity and crop quality [22]. We recently demonstrated that a specific extract of A. nodosum, Super Fifty (SF), reduces paraquat-induced oxidative stress in Arabidopsis thaliana and vegetable crops [12,75]. SF is a concentrated alkaline extract of the seaweed A. nodosum, which contains a range of unique carbohydrates such as fucoidan, alginate, and laminarin, as well as proteins and minerals [14].…”
Section: Discussionmentioning
confidence: 99%
“…Biostimulants can enhance the tolerance of plants to abiotic stresses and improve productivity and crop quality [22]. We recently demonstrated that a specific extract of A. nodosum, Super Fifty (SF), reduces paraquat-induced oxidative stress in Arabidopsis thaliana and vegetable crops [12,75]. SF is a concentrated alkaline extract of the seaweed A. nodosum, which contains a range of unique carbohydrates such as fucoidan, alginate, and laminarin, as well as proteins and minerals [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that non-growth hormone components in seaweed, such as polysaccharides, may be responsible for growth enhancing effects induced by SWE [132,133]. Polysaccharides are major components of brown seaweeds [134], and recent studies show that a particular commercial Ascophyllum nodosum (Super Fifty) extract high in polysaccharides modulates a range of processes at the transcriptomic, metabolic and lipid levels [135][136][137]. The authors demonstrate that these changes involve multiple pathways and culminate in significant changes at the phenotypic level, including: tolerance to oxidative stress and abiotic stresses; reductions in Reactive Oxygen Species (ROS); reductions in electrolyte leakage and increases in plant growth.…”
Section: Seaweed Extractsmentioning
confidence: 99%
“…The accumulation of ROS at levels that incur damage is referred to as oxidative stress, which can bring irreversible damage to cellular components and can compromise plant growth and yield. Priming with a commercial extract of A. nodosum (SuperFifty) has been shown to inhibit ROS production, and protects the model plant Arabidopsis thaliana and crops, tomato and pepper, from severe oxidative stress [135,136]. Priming and foliar application with SuperFifty led to a better tolerance against drought stress in Arabidopsis thaliana, with primed plants showing better development than control plants.…”
Section: Ascophyllum Nodosummentioning
confidence: 99%
“…The lipidomic assessment conducted by this team indicated that lipids associated with oxidative stress-induced cell death and chloroplast degradation, such as triacylglycerols (TAGs), declined in the SF pretreated plants. The beneficial effect of SF priming on reducing oxidative stress symptoms was further confirmed in the two important crops tomato and pepper, which were compared to Arabidopsis ([ 165 ]; Figure 2 ). In this study, quantification of primary metabolites showed accumulation of stress metabolites in plants exposed to oxidative stress alone but not in plants treated with SF and subsequently subjected to oxidative stress.…”
Section: Seaweed Extract Induced Stress Mitigationmentioning
confidence: 81%
“…In this study, quantification of primary metabolites showed accumulation of stress metabolites in plants exposed to oxidative stress alone but not in plants treated with SF and subsequently subjected to oxidative stress. Furthermore, the metabolome analyses identified characteristic metabolite signatures induced by SF in the three investigated species ([ 165 ]; Figure 2 ).…”
Section: Seaweed Extract Induced Stress Mitigationmentioning
confidence: 99%